The Influence of Environmental Sanitation Factors and Healthy Homes on Incident Stunting in the Mamboro Health Center Working Area, Palu City - Suarayasa, Ketut; Miranti, Miranti (Journal La Medihealtico, 2023)
The stunting rate in Palu City according to the results of the 2022 Indonesian Nutrition Status Survey (SSGI) is 24.7% or an increase of 0.7 digits compared to the 2021 figure of 23.9%. One of the sub-districts in the city of Palu which has a high prevalence of stunting is Taipa Sub-District in the Mamboro Health Center area with 24.7% or 108 cases out of 437 toddlers measured. The aim of the research is to analyze the relationship between healthy house factors and environmental sanitation with the incidence of stunting in the Mamboro Health Center working area. The type of research used is quantitative research with a case control research design. The sample size was 102 stunted toddlers in the case group and 102 normal toddlers in the control group. The results of the study showed that the healthy house factor had a significant relationship with the incidence of stunting with a value of p=0.002 (p<0.05). Respondents who own a house that does not meet the healthy requirements have a 2.82 times greater risk of having a stunted child (OR=2.82). Meanwhile, clean water facilities, latrine facilities, waste disposal facilities and waste disposal facilities have no relationship with the incidence of stunting (p<0.05). There is a relationship between healthy homes and the incidence of stunting in the Mamboro Community Health Center area (p=0.002), where respondents who have unhealthy homes are 2.82 times more likely to have stunted children (OR = 2.82).